Financial Management Maturity Level assessment of SIOC, in the context of the South African Mining Industry - Mbatha, Segomotso Boitumelo (University of the Witwatersrand, Johannesburg, 2024)
performance and identifying areas that require further maturation. The research was conducted within the specific context of SIOC in the mining industry of South Africa. The organisation launched a strategic initiative focused on four key pillars, namely, achieving zero fatalities, prolonging the lifespan of operations, attaining an additional $10 per ton margin by 2022 to reach a breakeven point at $35 per ton (in 2017 real terms), and becoming the Employer of Choice in South Africa. Three of the four strategic pillars were successfully achieved, except the breakeven objective. The primary objective of this research was to contribute to the current body of literature, and to advance knowledge of financial maturity models, as well as the relationship between financial maturity levels, organisational performance, and profitability. To assess the financial maturity of the organisation and enhance its performance and competitive advantage, a relevant financial maturity model was employed as a guide. Primary data was acquired through face-to-face semi-structured interviews and a questionnaire completed by all interviewees. The research included 20 interviews conducted with four financial management experts and 16 managers from various operational functions. The primary findings of the analysis suggested that the financial maturity level of the organisation is intermediate to good. The study recommends focusing on the simplification and accessibility of financial information, as well as the development of financial management at the junior to middle management levels
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Financial Maturity; SDG-8: Decent work and economic growth